Neurodegenerative disease and antioxidant biomarkers: A bidirectional Mendelian randomization study - Zhang, Qianqian; Li, Qingyang; Zhao, Huihui; Shu, Mingzhu; Luo, Maotao; Li, Yanan; Ding, Yu; Shi, Shiyu; Cheng, Xi; Niu, Qi (Frontiers in Neurology, 2023)
Previous observational studies have suggested that oxidative stress injury is correlated with neurodegenerative disease while its cause–effect remains unclear. Thus, we performed a bidirectional Mendelian randomization (MR) study with 3 main methods (Variance Weighted (IVW), Weighted Median (WM), and MR-Egger regression) to investigate the causal relationship between 11 oxidative stress injury biomarkers and 3 most common neurodegenerative diseases (Alzheimer’s disease (AD), Amyotrophic Lateral Sclerosis(ALS) and Parkinson’s disease(PD)) in the European population. The data of 11 oxidative stress injury biomarkers were selected from the open database by the most up-to-date Genome-Wide Association Studies (GWAS), while the summary statistics of PD and ALS were obtained from the International Parkinson's Disease Genomics Consortium(IPDGC) (33674 cases, and 449056 controls), and the International Amyotrophic Lateral Sclerosis Genomics Consortium (IALSC) (20,806 cases and 59,804 controls), respectively. For AD, we specifically used two recently published GWAS data, one from the International Genomics of Alzheimer's Project (IGAP)(21,982 cases and 41,944 controls), and the other from a large meta-analysis(71,880 cases and 383,378 controls) as validation data. Based on the Bonferroni correction (p<0.0015), we didn’t find the significant causal evidience for the oxidative stress biomarkers on neurodegenerative diseases, however, the reverse analysis found that AD was significantly related to the decrease in retinol (IVW: beta = −0.023, p = 0.0007; WM: beta = −0.025, p = 0.0121), while the same analysis was carried out between the AD validation database and retinol, and the results were consistent(IVW: beta = −0.064, p = 0.025). Moreover, AD on Glutathione S-transferase(GST), PD on Glutathione Peroxidase(GPX)as well as PD on uric acid (UA) also indicated potential causal-and-effect associations(IVW: p = 0.025; p = 0.027; p = 0.021, respectively). In short, although there was no sufficient evidence that oxidative stress has a significant causal effect on neurodegenerative diseases, this study revealed that genetically predicted AD was significantly related to the decrease in retinol, which provides a new insight into previous research and indicates the possibility to regard retinol as potential biomarker for the diagnosis and progress of AD.